2003
DOI: 10.1002/jcb.10330
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms of intestinal calcium absorption

Abstract: Calcium is absorbed in the mammalian small intestine by two general mechanisms: a transcellular active transport process, located largely in the duodenum and upper jejunum; and a paracellular, passive process that functions throughout the length of the intestine. The transcellular process involves three major steps: entry across the brush border, mediated by a molecular structure termed CaT1, intracellular diffusion, mediated largely by the cytosolic calcium-binding protein (calbindinD(9k) or CaBP); and extrus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
170
0
6

Year Published

2004
2004
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 250 publications
(179 citation statements)
references
References 25 publications
3
170
0
6
Order By: Relevance
“…Calcium containing substances are required by children, pregnant and lactating woman and also osteoporosis people for bones and teeth development. The value of calcium is close to the recommended daily allowance of 15,000 ppm per day for both adults and children [14]. While for osteoporosis people, the calcium intake is higher than the recommended daily allowance.…”
Section: Atomic Absorption Spectroscopysupporting
confidence: 50%
See 1 more Smart Citation
“…Calcium containing substances are required by children, pregnant and lactating woman and also osteoporosis people for bones and teeth development. The value of calcium is close to the recommended daily allowance of 15,000 ppm per day for both adults and children [14]. While for osteoporosis people, the calcium intake is higher than the recommended daily allowance.…”
Section: Atomic Absorption Spectroscopysupporting
confidence: 50%
“…CaCO3 is the most prevalent form of a calcium supplement [9][10][11][12]. The low efficacy of CaCO3 may be overcome by applying nano-sized materials, which can induce cellular uptake by endocytosis [13][14] In this work, nano-sized CaCO3 was obtained by milling process and this CaCO3 nano particle was added to purified diet with the various concentrations. CaCO3, is the most commonly used mineral as a source of inorganic salt.…”
Section: Introductionmentioning
confidence: 99%
“…1), consisting of passive entry of Ca 2+ across the luminal or apical membrane, cytosolic diffusion of Ca 2+ bound to vitamin D 3 -sensitive Ca 2+ -binding proteins (calbindin-D 28K and/or calbindin-D 9K ) and active extrusion of Ca 2+ across the opposite basolateral membrane by the Na + -Ca 2+ -exchanger (NCX1) and/ or Ca 2+ -ATPase (PMCA1b; Bronner 2003;Hoenderop et al 2002b). The molecular identity of the apical Ca 2+ entry pathway remained elusive until the epithelial Ca 2+ channels TRPV5 (previously named ECaC1; Hoenderop et al 1999) and TRPV6 (previously named Ca 2+ transporter 1) were identified (Montell et al 2002b;Peng et al 1999).…”
Section: Introductionmentioning
confidence: 99%
“…The 30-year-old paradigm that calcium is ferried through cytosol by mobile calcium-binding proteins (calbindins) remains widely accepted (3)(4)(5)(6)(7)(8)(9). Calbindins are thought to facilitate the naturally poor diffusion of calcium in cytosol and simultaneously buffer calcium at safe concentrations.…”
mentioning
confidence: 99%